Clinical Application and Feasibility of MRI-Guided Breast Biopsy of Breast Minimal Lesions in Chinese Population - Wang, Jie; Song, Ying; Liu, Jiaqi; Meng, Xiangzhi; Xing, Zeyu; Zhang, Menglu; Ye, Feng; Wang, Xin; Wang, Xiang (Frontiers in Oncology, 2020)
Objectives: Some breast lesions are not visible on mammography or ultrasonography, and magnetic resonance imaging (MRI) become the only way to monitor these lesions. The purpose of this study was to evaluate the clinical application of MRI-guided biopsy and MRI-guided wire localization of breast minimal lesions in Chinese population. Methods: We evaluated 95 patients (the most patients of known in China) from August 2013 to December 2017. All the patients were scanned with a 1.5-Tesla MRI system (GE Medical Systems, America) in the prone position using a bilateral 8-channel phased-array breast coil and underwent MRI-guided wire localization or MRI-guided biopsy. Results: MRI-guided wire localization and MRI-guided biopsy were successfully performed in 87 patients with 88 lesions (100%, 88/88). After biopsy or surgery, 36 of 88 lesions (40.91%) were malignant, and 52 of 88 lesions (59.09%) were benign. Thirty-nine of 88 lesions (44.32%) were masses, and 49 of 88 (55.68%) showed non-mass enhancement. Statistical analysis showed there was no significant correlation between the malignancy rate and the type of lesion on MRI (P = 0.27). In this study, the rate of malignancy for Breast Imaging-Reporting and Data System (BI-RADS) 5 lesions was 100% (2 of 2) compared with 44.44% for BI-RADS 4C lesions (4 of 9), 42.42% for BI-RADS 4B lesions (14 of 33), and 36.36% for BI-RADS 4A lesions (16 of 44). Conclusions: MRI-guided wire localization with subsequent surgical biopsy and MRI-guided biopsy are safe and effective tools for breast minimal lesions.